2014
DOI: 10.2131/jts.39.179
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil exacerbates concanavalin A induced hepatitis through promoting hepatocyte apoptosis and altering immune cell populations

Abstract: -The development of hepatitis is associated with the infiltration and activation of immune cells in liver. N-3 polyunsaturated fatty acids (n-3 PUFAs) rich fish oil (FO) is used to prevent and treat inflammatory diseases. But, the effects of dietary FO on autoimmune hepatitis remain largely unknown. In this study, Concanavalin A (Con A) induced hepatitis was used to evaluate the actions of dietary FO. Unexpectedly, 2-week FO treatment had not shown any protection, on the contrary, exacerbated liver injury in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…We have also observed an elevation in proinflammatory cytokines in ConAinjected rats. Our present findings agree with previous studies in which a similar elevation of inflammatory cytokines in ConA-induced hepatitis was reported [32][33][34][35][36]. We observed that eugenol pre-and concomitant treatment suppressed the ConA-induced elevation of proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…We have also observed an elevation in proinflammatory cytokines in ConAinjected rats. Our present findings agree with previous studies in which a similar elevation of inflammatory cytokines in ConA-induced hepatitis was reported [32][33][34][35][36]. We observed that eugenol pre-and concomitant treatment suppressed the ConA-induced elevation of proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%